Response of a turbulent boundary layer to lateral roughness discontinuities - Wang, Hua, author; Nickerson, Everett C., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1972)
The structure of the turbulent boundary layer on a flat plate consisting of alternate, longitudinal strips of smooth and rough (Sand paper, Grit 4) surfaces parallel to the direction of the flow has been investigated. Measurements of mean velocity, wall shear stress, turbulent intensities, turbulent shear stresses and energy spectra of the streamwise turbulent velocity were obtained. The flow field can be subdivided into three regions. These are: (a) the "smooth" region along the centerline of each smooth strip; (b) the "rough" region along the centerline of each rough strip; and (c) the "intermediate" region lying between the smooth and the rough regions. In both smooth and rough regions, the flow conditions are found to be nearly analogous to those in two-dimensional boundary layers over smooth and rough walls, respectively. In the intermediate region the wall shear stress was found to adjust itself very rapidly to the local conditions of the wall while going from the smooth to the rough region. The vertical distribution of mean velocity can satisfactorily be expressed by the two-dimensional descriptions for the law of the wall and the velocity-defect law. However, the two laws are not universal but form a family of curves depending on the local wall shear stress. The spanwise change from smooth-wall conditions to rough-wall conditions will induce a weak cross-flow directed from the rough to the smooth region near the wall. A theoretical description of the turbulent shear stress -vw which is responsible for the generation of this cross-flow has been presented. The spanwise adjustment of turbulent quantities to local conditions of the wall takes place at a slower rate than does the wall shear stress. The normalized spectra of the streamwise turbulent velocity remains largely unaffected by the surface configuration investigated here.
CER71-72-HW-ECN51.
July 1972.
Prepared under Office of Naval Research contract no. N00014-68-A-0493-0001 project no. NR 062-414/6-6-68 (Code 438) U.S. Department of Defense Washington, D.C.
Circulating copy deaccessioned 2020.
Keywords: Air flow; Turbulence; Boundary layer; Atmospheric circulation